Review of Marie Vieux Chauvet’s Theatres: Thought, Form, and Performance of Revolt - Kasia Mika (European Review of Latin American and Caribbean Studies, 2020)
'Marie Vieux Chauvet’s Theatres: Thought, Form, and Performance of Revolt', edited by Christian Flaugh and Lena Taub Robles. Brill, 2019